Do ethnic enclaves impede immigrants' integration? Evidence from a quasi-experimental social-interaction approach - Alexander M. Danzer; Firat Yaman (Center for Economic Studies and ifo Institute (CESifo), 2012)
It is widely debated whether immigrants who live among co-ethnics are less willing to integrate into the host society. Exploiting the quasi-experimental guest worker placement across German regions during the 1960/70s as well as information on immigrants' inter-ethnic contact networks and social activities, we are able to identify the causal effect of ethnic concentration on social integration. The exogenous placement of immigrants switches off observable and unobservable differences in the willingness or ability to integrate which have confounded previous studies. Evidence suggests that the presence of co-ethnics increases migrants' interaction cost with natives and thus reduces the likelihood of integration.
Keywords: J15; R23; J61; 330; immigrants; integration; enclaves; political participation; culture; social interaction; guest workers